Avaliação de técnicas de captação de água de chuva para recuperação ambiental na região semi-árida do Vale do Jequitinhonha - Norma Angelica Hernandez Bernal (2007)
Brazil, as many other developing countries, has to face the problem of freshwater availability to reduce environmental and social vulnerability, mainly in its semiarid region. In the semiarid region of the Minas Gerais state the average annual precipitation is 800mm, which is concentrated in 4 months, with an elevated evaporation rate all through the year.Mismanagement of water and soil resources has caused the degradation of the fragile ecosystem (Caatinga) that exists in this region which is considered among the poorest in Brazil, and such environmental situation worsens economic and social conditions of the population living there. In this study, the implementation of rainwater harvesting techniques (RWH) is considered as an alternative to increase soil water infiltration, restore soil properties as well as to restore the vegetation in two 800m2 experimental plots. The objective of this study, carried out without artificial irrigation, was to evaluate the efficiency of four differentmicro-rainwater harvesting techniques (runoff farming) to yield water infiltration in order to increase soil moisture. The runoff farming systems tested were: a) negarim (S1); b) Semicircular bunds (S2); c) Contour bunds (S3); and d) Contour ridges (S4). In each microcatchment one tree was planted. A 200 m2 area without any treatment or RWH technique was used as a control area. Two growth parameters on Psydium guajava (guava) and Manguifera indica (mango) trees were used as indicators of the efficiency on water availability on soil profile to enhance plant growth. Soil stability tests, superficial infiltration rate and humidity percentage on soil profile were also, measured. Monthly photographs were shot to record qualitative information on the development of the plants, as well as the conditions of the RWH structures. Qualitative and quantitative data have shown that the Contour bunds (S3) and Contour ridges (S4) systems are more efficient than the other two, at different levels, on retaining soil humidity allowing a good development of the plants, evenalong the dry period. It was also observed that the Contour ridges (S4) system was efficient in the restoration of the quality of soil aggregates, minimizing erosion processes. These techniques, along with other soil and water conservation measures, can serve as a management tool to restore natural resources as well as an alternative for the humancommunities to use in a sustainable way the local soil and water resources, improving life conditions in this region.